Excess molar volumes and viscosity behaviour of binary mixtures of aniline/or N, N-dimethylaniline with imidazolium ionic liquids having triflate or bistriflamide anion. (June 2017) - Soldatović, Danijela; Vuksanović, Jelena; Radović, Ivona; Višak, Zoran; Kijevčanin, Mirjana
Highlights: Measurements of density and viscosity of aniline/ N, N -dimethylaniline+ILs mixtures. Detailed thermodynamic interpretation of molecular interactions is performed. Strong attractive interactions are present in three completely miscible mixtures. Aniline + [bmim][OTf] exhibits partial miscibility. Abstract: In this study, densities and viscosities of four binary systems aniline/ N, N -dimethylaniline + 1-butyl-3-methylimidazolium triflate ([bmim][OTf]) and aniline/ N, N -dimethylaniline + 1-butyl-3-methylimidazolium bis(trifluoromethylsulfonyl)imide ([bmim][NTf2 ]) were measured at atmospheric pressure and within the temperature range T = (288.15 to 333.15) K. Excess molar volumes V E, viscosity deviations Δ η and excess molar Gibbs energies of activation of viscous flow ∆G ∗E were calculated and the results were fitted to a Redlich-Kister polynomial equation. Also, enthalpic and entropic parts of the ∆G ∗E function were determined, at the same composition, for three studied systems that exhibit complete miscibility, since aniline + [bmim][OTf] is a partially miscible system. Considering the calculated thermodynamic properties, molecular interactions in the investigated binary systems were analysed and are discussed.